Case reports: a variety of clinical presentations and long-term evolution of Bochdalek hernias - Frey, Sebastien; Chazal, Maurice; Sejor, Eric; Baque, Patrick; Mouroux, Jerome (Frontiers in Surgery, 2023)
Bochdalek hernias are the second most common congenital diaphragmatic hernias after Larrey hernia. The failure of closure of the pleuroperitoneal membrane results in a posterolateral foramen, which can remain silent until adulthood. They remain a rare pathology with nearly a hundred cases published. Its clinical presentation is variable, making its diagnosis challenging for clinicians. Additionally, the symptoms are not necessarily representative of the content of the hernia. Its management is balanced between the abdominal and the thoracic approaches. However, no guidelines or algorithms are available to help surgeons in the decision-making process. We report here four consecutive cases of symptomatic Bochdalek hernias. Each case has a singular presentation and we share how they were approached at our institution. In particular, this series shows no reoccurrence in 10+ years of follow-up in two cases and 20+ in one case, underlying the importance of surgical management when Bochdalek Hernias are symptomatic.